KONSEP PENGATURAN NETRALITAS ASN DALAM PEMILU DAN PILKADA SERENTAK TAHUN 2024 - Dairani Dairani; Ach. Fadlail (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2023)
The neutrality of ASN in practical political activities is a problem that has not been resolved by the government or the election organizers themselves. Thus far, 2024 has been the biggest political year in the history of Indonesian democracy because it elects the president and his deputy and legislative members from the center to the regions. In the same year, regional head elections were held simultaneously throughout Indonesia. Thus, appropriate efforts and steps are needed to overcome the problem of ASN neutrality. This article aims to find the concept of regulating ASN neutrality in the 2024 simultaneous elections and future elections. Normative legal research was chosen as an analytical tool to answer the legal issues that are the focus of the study in this article. The results of the research show that efforts to prevent ASN neutrality in elections and Regional Head Elections can be carried out by strengthening them institutionally to maximize their duties and functions such as KASN, KPU_Bawaslu to DKPP, both of the ASN elements themselves by building political awareness through political and legal education. The Regional Government, BKN, BKD, or each government agency can initiate it. In conclusion, the joint commitment of all parties, including the KPU-Bawaslu DKPP to ASN and respective government agencies, is the main key in closing the space for ASN involvement in practical political activities, especially in the simultaneous and regional elections in 2024.